In this Issue - Michael Scriven (The Evaluation Center at Western Michigan University, 2006)
In our continuing coverage of evaluation activities around the world, at their varied levels of technical complexity, this issue brings two reports from China-one about a marshland environmental protection and recovery effort, and one about a very large effort at family support in Shanghai. On the new and important sub-area in evaluation that addresses the evaluation of scientific and technological research, we have three pieces. The editorial is a reflection on the first five issues of this journal, now totaling almost 1,000 pages, a good moment for reflection-and for your feedback on it!